Dokumentum 69-70. - Iparterv Designers Budapest (Budapest : Iparterv Designers, 1969)
Bak, Imre ; Baranyay, Andras ; Frey, Krisztián ; Hencze, Tamas ; Keserü, Ilona ; Konkoly, Gyula ; Lakner, Laszlo ; Major, János ; Mehes, Laszlo ; Nadler, Istvan ; Palfalusi, Attila ; Siskov, Ludmil ; Tot, Endre
biog., tent. [1 p.]
Hongaars
Iparterv II, Iparterv Designers Budapest, 1969-10-24
boek